KESETARAAN DAN KEADILAN GENDER (KKG) DAN TANTANGAN GLOBAL - Arjani, Ni Luh (INPUT Jurnal Ekonomi dan Sosial, 2012)
The Gender Equality and Justice is the problem that has been discussed globally since hundred years ago in order to reduce the gender inequality and injustice among people. The commitment to reduce the gender inequality valid for all aspects of human life including education, economy, politic, social, and culture. The importance of the discussion even become one from eight point of the international commitment through The Millennium Development Goals (MDGs) which is promote by United Nation (UN). The emerge of attention in gender issue is being in accordance with the shift of development paradigm from the security and stability (security) approach into the welfare and equality (prosperity) approach or from the production into the humanity approach in more democratic and open atmosphere. The strong relation to the construction of social and culture that rooted in society border the achievement of gender equality and justice. But with the strong struggle and continuous effort the gender ideology that tends to bring the detriment to one gender will be eliminated successfully. As the conclusion, if the motivation occurs among the people, it shows that our society is able to ful? ll one of the agreements of Millennium Development Goals (MDGs) which is also become the international commitment.
Keywords: Equality and Justice, Gender, MDGs